The Phenomenon Of 'Cancel Culture' In Indonesia: Between Ethics, Social, And Politics In Digital Space - Widhiarcani Matradewi, Ni Ketut (PT. Anagata Sembagi Education, 2024)
The development of information technology and social media has brought about significant transformations in social interactions, creating a complex and inclusive digital space. However, the phenomenon of cancel culture in Indonesia creates complex ethical, social and political challenges. Cancel culture often triggers collective judgments that ignore principles of justice and social responsibility, exacerbating social polarization and expanding the space for extreme views. This study uses a descriptive qualitative approach to explore the dynamics of cancel culture, involving research subjects such as social media users, public figures, communication experts and political actors. The results reveal that the lack of regulation and digital literacy contributes to the manipulation of digital space, where acts of mass judgment are often repressive and used as a politicization tool. To overcome this challenge, a holistic approach is needed that integrates legal regulation with the strengthening of digital literacy that builds critical and ethical awareness in the digital space.